Does customer-based reputation add to social and mass media reputation in judging social responsibility of banks? - Rebelo, R. (2020)
Purpose: Reputation is a critical asset for finance and banking organizations where the mere suspicion of a problem suffices to trigger media turmoil with high risk of market share losses. Investing in media to build reputation has been therefore a priority for banks. However, another source of reputation may stem from direct front-office contact and it is yet unknown to which extent it plays a role when confronted with the widespread social and mass media reach. This study aims at testing the extent of the importance of customer-based reputation, as against media-based reputation, in explaining customer outcomes.